New Attitude to the Great Silk Road - I. S. Zonn; Uyichtzao Tjan (Проблемы постсоветского пространства, 2017)
The Great Silk Road existed more than 2000 years and has played an important role in the development of civilizations and trade and economic relations. New geopolitical conditions that have emerged over the last decades in Central Asia, and the increasing role of China in the world economy have come to understand the need of reviving the Great Silk Road.